Health and Wellness Tourism Development on Global Markets in Pandemic - Oborin, Matvey (Anais Brasileiros de Estudos Turísticos, 2022)
International crisis makes health and wellness tourism a powerful catalyst for the regional development in global economic competition. However, this was health and wellness tourism most affected by the COVID-19 pandemic. The article identifies the main economic consequences of COVID-19 for the field health and wellness tourism and for industries that depend on it. The state support is especially needed for the industry. The medical tourism market is now in crisis. This is due to the epidemiological health threats, a decrease in entrepreneurial activity, sharp drop in demand for both medical and tourism services because of decrease in the income of the population and the inability to use the existing infrastructure. The way out of this situation is possible only with the adoption of competent management decisions that could combine both the state support and provision for the most affected sectors of the national economy, and our own initiatives related to the introduction of changes in the organization and management of relevant business processes.